Automatic questions generation based on keywords using language models - Tomasz Gniazdowski; Marek Bazan; Maciej E. Marchwiany (International Journal of Electronics and Telecommunications, 2025)
In this paper, we presented a novel method for question generation, one of the most impactful NLP tasks in contacts of user interfaces, chatbots and intelligent assistants with a user. Our method outperforms commonly used methods in terms of quality and speed of question generation. Additionally, we benchmarked the most used methods of question generation that are based on the usage of Large Language Models in a fewshot approach as well as finetuned to that task. Our work is done for the Polish language, it has one of the most challenging and complex grammars, which makes the task even more difficult.